ANALISIS PENGARUH KUALITAS WEBSITE PPDB TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN REGRESI LINIER BERGANDA - Silvia, Hana; Aprilia Kartini, Kasih; Dafa, Muhammad; Nuris, Nuzuliarini; Diantika, Sri (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
In today’s digital era, many individuals rely on websites to quickly and efficiently obtain information. Vocational High Schools (SMK) are not left behind in leveraging modern technology through the website-based New Student Admission System (PPDB). While this system offers convenience, crucial questions arise regarding the quality of the PPDB Bersama website and its impact on user satisfaction. This study aims to analyze the effect of website quality on user satisfaction at SMKS 28 Oktober 1928 II. Utilizing the Webqual 4.0 method, the research identifies three independent variables: usability, information quality, and interaction quality, with user satisfaction as the dependent variable. Data processing was conducted using Excel and SPSS. The results indicate that all independent variables significantly contribute to user satisfaction. The coefficient of determination (R²) of 0.813 suggests that 81.3% of user satisfaction can be explained by these variables, while the remaining percentage is influenced by other factors. These findings affirm that the quality of the PPDB Bersama website has a significant positive impact on user satisfaction at SMKS 28 Oktober 1928 II, highlighting the importance of enhancing and maintaining platform quality to support better educational processes.